TANGGUNG JAWAB PEMBERI KERJA TERHADAP PEMENUHAN HAK PEKERJA PEREMPUAN PADA SALAH SATU RUMAH MAKAN DI KOTA PONTIANAK - NIM. A1011211311, CITRA AMANDA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Female workers are a group with specific needs and vulnerabilities in employment relationships, both biologically Emand socially. Therefore, the protection of female workers